Effect of Vitamin E Use on Hot Flash Reduction in Menopausal Women - Sibagariang, Fadlullah Asykari; Sinaga, Rahmanita (Buletin Farmatera, 2027)
Abstract : Hot flash is a sudden hot sensation that usually appears in the chest, neck, and face, accompanied by sweating, heart palpitations, and can be triggered by a warm environment, hot drinks, or emotional stress. These symptoms are often the main reason women seek medical care during perimenopause because it can interfere with quality of life. Vitamin E, with its antioxidant properties, has been shown to be able to reduce the intensity and frequency of hot flashes through improved adrenal function. This study aims to assess the effect of Vitamin E administration on the reduction of hot flashes in menopausal women. The method used was an experiment with administering Vitamin E daily for four weeks to the study subjects. Data was obtained from a questionnaire of hot flash patients in 2022 at Bhayangkara Hospital Medan based on a doctor's examination and the HFRS scale. The results of the statistical test showed a P-Value of 0.000, lower than alpha 0.05, so the null hypothesis was rejected. In conclusion, Vitamin E is significantly effective in reducing hot flashes in menopausal women.